The Influence of a Competitive Field Hockey Match on Cognitive Function - Malcolm, Rachel; Cooper, Simon; Folland, Jonathan P.; Tyler, Christopher J.; Sunderland, Caroline (Frontiers in Human Neuroscience, 2022)
Despite the known positive effects of acute exercise on cognition, the effects of a competitive team sport match are unknown. In a randomized crossover design, 20 female and 17 male field hockey players (19.7 ± 1.2 years) completed a battery of cognitive tests (Visual Search, Stroop, Corsi Blocks, and Rapid Visual Information Processing) prior to, at half-time, and immediately following a competitive match (or control trial of seated rest); with effect sizes (ES) presented as raw ES from mixed effect models. Blood samples were collected prior to and following the match and control trial, and analysed for adrenaline, noradrenaline, brain derived neurotrophic factor (BDNF), cathepsin B, and cortisol. The match improved response times for a simple perception task at full-time (ES = -14ms; P<0.01) and response times on the complex executive function task improved at half-time (ES = - 44 ms; P<0.01). Working memory declined at full-time on the match (ES = -0.6 blocks; P<0.01). The change in working memory was negatively correlated with increases in cortisol (r =-0.314, P=0.01; medium), as was the change in simple perception response time and the change in noradrenaline concentration (r =-0.284, P=0.01; small to medium). This study is the first to highlight the effects a competitive hockey match can have on cognition. These findings have implications for performance optimisation, as understanding the influence on specific cognitive domains across a match allows for the investigation into strategies to improve these aspects.